Ocular and systemic pharmacokinetics of BI-X, a nanobody targeting VEGF and Ang-2, after intravitreal dosing in cynomolgus monkeys – Evidence for half-life extension by albumin. (April 2021) - Fuchs, Holger; Chen, Lin-Zhi; Low, Sarah; Yu, Hongbin
Abstract: Half-life extension strategies to reduce the intravitreal dosing frequency of biomolecules for the treatment of retinal neovascular diseases are attracting increasing interest. This study investigated ocular and systemic pharmacokinetics of the trivalent nanobody BI-X (with affinity to VEGF, Ang-2 and human albumin) in cynomolgus monkeys after intravitreal injection. BI-X concentrations were measured in serial samples of plasma, vitreous humor, aqueous humor and retina. Ocular pharmacokinetics of BI-X exhibited two phases. Initially up to 2–4 weeks after dosing, BI-X concentrations in vitreal, aqueous humor and retina declined with half-lives of around 3 days, which is comparable to macromolecules with a similar molecular weight. Thereafter, only vitreal concentrations were measurable, with a terminal half-life of 13.2 days, which is considerably longer than expected based on the BI-X molecular weight or hydrodynamic radius. It is hypothesized that binding of BI-X to low levels of intraocular albumin resulted in this half-life extension. BI-X was detectable in plasma up to 10 weeks post-dosing. Plasma pharmacokinetics of BI-X exhibited a similar biphasic disposition profile to the vitreous body, with a terminal half-life of 11.8 days, thus reflecting input kinetics from the eye. In conclusion, an important half-life extension principle based on vitreal albumin binding could be confirmed in a primate model, and the data obtained can potentially be translated to humans taking into account the differing vitreal albumin concentrations.